A broadband utopia [fast broadband connectivity]. - Cherry, S. (IEEE spectrum)
The Utah Telecommunication Open Infrastructure Agency (Utopia) promises to deliver to each of its 3,000 subscribers high-speed Internet access, telephony and television programming through a fiber-optic cable at data rates that reach 30 megabits per second. Encompassing 14 cities in the northeastern Utah, the optical-fiber broadband network is expected to soon reach speeds of 50 and even 100 Mb/s. Because Utopia sends TV programming as Internet packets, it puts a huge reservoir of bandwidth at the disposal of its providers. In addition to its dedicated bandwidth connections, Utopia relies on the Ethernet standard to carry Internet protocol data packets all the way from the central office to the individual subscriber without changing the format, greatly simplifying the network.